2007
DOI: 10.1021/pr060689s
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics-Based Method for the Assessment of Marine Pollution Using Liquid Chromatography Coupled with Two-Dimensional Electrophoresis

Abstract: Using a proteomic approach, we have developed a new method for the assessment of marine pollution that generates highly reproducible protein expression patterns and it is simple and scalable. The protocol is based on applying liquid chromatography (LC) coupled with two-dimensional electrophoresis (2-DE) to analyze changes in the protein expression pattern after exposure to marine pollution. The digestive gland of the sentinel "blue mussel" (Mytilus edulis) was batch-processed through a simple cell fractionatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 57 publications
1
41
0
Order By: Relevance
“…Using protein expression profiles, several authors have reported on the use of proteomic approaches for the establishment of ''protein signatures'' after exposure to a variety of environmental contaminants including PCBs, polyaromatic hydrocarbons (PAHs), heavy metals [50,51], and crude oil [52][53][54]. Additionally, proteomics has been used to compare profiles of mussels residing in polluted areas to those of reference sites [55,56]. Not only have the proteomes of these bivalve species been evaluated when exposed to individual contaminants, but to mixtures as well [57].…”
Section: Aquatic Invertebratesmentioning
confidence: 99%
See 1 more Smart Citation
“…Using protein expression profiles, several authors have reported on the use of proteomic approaches for the establishment of ''protein signatures'' after exposure to a variety of environmental contaminants including PCBs, polyaromatic hydrocarbons (PAHs), heavy metals [50,51], and crude oil [52][53][54]. Additionally, proteomics has been used to compare profiles of mussels residing in polluted areas to those of reference sites [55,56]. Not only have the proteomes of these bivalve species been evaluated when exposed to individual contaminants, but to mixtures as well [57].…”
Section: Aquatic Invertebratesmentioning
confidence: 99%
“…Conversely, upwards of 39 C. riparius larval proteins were identified through MALDI-TOF-MS and spectra blasted against the National Center for Biotechnology Information nonredundant protein database, or Mass Spectrometry protein sequence database (MSDB) with MS-Fit program [67]. However, many proteomic studies with aquatic invertebrates have identified, on average, 15 proteins [8,43,56,66], indicating the problem with matching amino acid sequences across species. Some studies have tried various techniques to improve protein identification by incorporating fractionation of samples, as well as the use of nanospray-ion trap MS, followed by database searching and de novo sequencing [3].…”
Section: Aquatic Invertebratesmentioning
confidence: 99%
“…Some authors have reported that environmental stress such as variation in salinity and temperature [96] or exposure to environmental contaminants such as heavy metals, xenoestrogen, and chlorinated compounds [94,97,98] has an impact on protein expression in different tissues of relevant aquatic organisms. Although gel-free methods using surface-enhanced laser desorption/ionization (SELDI) mass spectrometry have been investigated [99][100][101], environmental biomarker discovery still relies mainly on 2D gel electrophoresis and, to our knowledge, is lacking for aquaculture production [102][103][104]. However, there is no doubt that using a proteomic approach in combination with other biomarkers at physiological, behavioral, and biochemical levels will give a more precise set of biomarkers for assessing the exposure of penaeid shrimp to drugs and chemicals.…”
Section: Further Developmentsmentioning
confidence: 99%
“…Digestive glands were processed following a protocol for sample prefractionation and 2-DE protein separation already described (Amelina et al, 2007). Briefly, digestive glands were homogenized with the aid of a pestle and AG®501-X8 Resin glass beads (BioRad Laboratories, Inc., Hercules, CA, USA) in a homogenization buffer containing a protease inhibitor cocktail.…”
Section: Proteomics Analysismentioning
confidence: 99%
“…Precipitated proteins were solubilized in a solubilization buffer described by Rabilloud with some modifications (Rabilloud, 1998;Amelina et al, 2007), alkylated with 30 mM iodoacetamide (IAA) in darkness and mixed with a rehydration buffer previous to the isoelectrofocusing (IEF) step. Proteins (300 µg) were loaded in the PROTEAN® IEF Cell (BioRad Laboratories) tray and IPG strips (11 cm, pH range of 4-7, BioRad Laboratories) placed on top.…”
Section: Proteomics Analysismentioning
confidence: 99%